Pengembangan Multimedia Pembelajaran Berbasis Augmented Reality Sebagai Upaya Menangkal Paham Radikalisme di Kalangan Pelajar SMA Kota Banjarmasin - Murjani Murjani; Moh. Iqbal Assyauqi; Sahari Sahari; Yokke Andini (Jurnal Ilmiah Iqra', 2021)
Development of Augmented Reality-Based Learning Multimedia as an Effort to Counter Radicalism Among Banjarmasin City Senior High School Students. The flow of radicalism in Indonesia has been followed almost simultaneously with the rapid development of information and communication technology (ICT) over the last two decades. This is certainly a great opportunity for education practitioners to take advantage of ICT-based media in learning to improve the quality of education. The emergence of various media-based learning systems is a tangible form of integration of ICT and learning. Augmented Reality is a technology that combines virtual objects are two-dimensional (2D) / three-dimensional (3D) into a real environment. The use of technology in Augmented Reality is expected to provide a more concrete learning experience about the dangers of radicalism among students. The development model used is the adaptation development model from Dick & Carey, Borg & Gall, and Kemp & Dayton which includes five stages, namely (1) needs analysis, (2) product development planning stages, (3) product development stages, ( 4) product evaluation stage, and (5) final product. The results of the development show that the learning program developed has met the effectiveness of the assessment aspects of the material experts, namely: the content aspect, and the learning / instructional aspect. The results of the material expert evaluation show that this learning product is in the very good category in the content aspect with an average scale of 4.13. The learning / instructional aspect with a mean scale of 4.25 is in the very good category.Augmented Reality-based learning multimedia as an effort to ward off radicalism among high school students have met the feasibility of communication, display design, and program aspects by media experts. The results of the evaluation show that all aspects of the assessment evaluated by media experts fall into the good category, namely the communication aspect with a mean of 4 (good category), the display design aspect with an average scale of 4 (good category), and the program aspects with an average scale of 4 (good category). Broadly speaking, all aspects evaluated by material experts fall into the good category, so Augmented Reality-based learning multimedia as an effort to ward off radicalism among high school students is effective in terms of the media aspect